Nutrition and Exercise Strategies to Prevent Excessive Pregnancy Weight Gain: A Meta-analysis - Craemer, Katherine A.; Sampene, Emmanuel; Safdar, Nasia; Antony, Kathleen M.; Wautlet, Cynthia K. (American Journal of Perinatology Reports, 2019)
Objective To evaluate nutrition-only, exercise-only, and nutrition-plus-exercise interventions for optimizing gestational weight gain (GWG) based on the 2009 Institute of Medicine (IOM) guidelines.Study PubMed, Google Scholar, and 2015 Cochrane Review were searched. Analysis of variance was used to determine if significant GWG differences exist between strategies, with additional subanalyses on overweight (OV) or obese women based on 2009 IOM guidelines.Results Of 66 identified studies, 31 contributed data (n = 8,558). Compared with routine prenatal care, nutrition-only interventions were significantly associated with reduced GWG and are most likely to produce weight gain within IOM recommendations (p = 0.013). Exercise-only (p = 0.069) and nutrition-plus-exercise (p = 0.056) interventions trended toward GWG within IOM guidelines, but did not reach statistical significance. Supervised (p = 0.61) and unsupervised (p = 0.494) exercise programs had similar effectiveness. Subanalyses on OV or obese women produced similar results to studies that did not differentiate results based on body mass index: nutrition only (p = 0.011), exercise only (p = 0.308), and nutrition plus exercise (p = 0.129).Conclusion Preventing excessive GWG is crucial, especially for OV or obese women. In the current study, nutrition-based intervention is the health system strategy that showed significant impact on preventing excessive GWG compared with routine prenatal care. Among women who are OV or have obesity, nutrition-only interventions hold the most promise compared with routine prenatal care.
Keywords: nutrition intervention; exercise intervention; pregnancy; weight gain; obesity